The Effect of Support From Secondary Caregiver Network on Primary Caregiver Burden: Do Men and Women, Blacks and Whites Differ?. (4th May 2022) - Liang, Jiaming; Aranda, María P; Jang, Yuri; Wilber, Kathleen; Chi, Iris; Wu, Shinyi
Abstract: Objectives: Many older adults receive informal care from multiple caregivers, including support from a primary caregiver and a secondary caregiver network (SCN). This study examined the association between SCN support and primary caregiver burden, and whether the association varies across women and men, Black and White. Methods: Data came from the 2015 National Health and Aging Trend Study and the National Study of Caregiving, including non-Hispanic White and Black men and women who were identified as primary caregivers ( n = 967) and their secondary caregivers ( n = 2, 253). SCN support was indicated by (a) care domain overlap and (b) proportion of caregiving by SCN. Multiple regression models were estimated for the analyses. Results: Both SCN support variables were found to reduce primary caregiver burden, and the effect of proportion of caregiving by SCN was found to vary by gender–race groups. With the increase of the proportion of caregiving by SCN, both Black and White women caregivers tend to experience faster decrease in caregiver burden than Black men. Discussion: Our findings support the role of SCN in reducing primary caregiver burden and demonstrate that the benefit of SCN support varies across the 4 gender–race groups. The results indicate that it is imperative to further examine caregiving experience and protective mechanisms of SCN support using an intersectional perspective.